Job Satisfaction and Organizational Justice As Determinant of Turnover Intention: A Study Among Global Support Executives (GSEs) in HSBC Call Center Cyberjaya Malaysia - Nagaindran, Banu (2006)
Turnover intention is basically the manifestation of one's inner feeling about his or her job. In other words, it is an emotional state linked to one's job, which would effectively be translated into job behaviors, and in due course would positively/negatively affect the overall performance of an employee. In this context, the level of turnover intention experienced by the employee is greatly influenced by various internal and external factors. To mention a few, they might include the nature of the job itself, management practices, human resources systems and policies, work place condition, co-workers/peers and the other personal feelings normally reflects the aggregate effects of many attributing factors. Therefore, attempts to single out any specific influential factor in explaining the level of turnover intention among employees would proof to be less objective and costly. This study was commenced to examine the level of turnover intention among Global Support Executives of HSBC Call Center, Cyberjaya. That being the case, it was also focusing on few selected variables believed to have a constructive influence on the research question, turnover intention. This task entails a closer look at examining the relationship between two identified variables, ie; job satisfaction and organizational justice and the level of turnover intention experienced by HSBC.